Perbandingan Kualitas Es di Lingkungan Universitas Al Azhar Indonesia dengan Restoran Fast Food di Daerah Senayan dengan Indikator Jumlah Escherichia coli Terlarut - Dewi Elfidasari (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2011)
Escherichia coli (E. coli) is bacteria that usually be an indicator of faecal contamination in the beverages test. This study was conducted to determine the level of hygiene or the purity of ice that is consumed by people in the surrounding of University of Al Azhar Indonesia (UAI) and Senayan, South Jakarta. In this study, E. Coli serves as an indicator. Performed several laboratory tests with the test sample contained ice in sampling three points from UAI food court, street vendors around the UAI, and fast food restaurants in the area of Senayan. Totally we have 24 samples whereas 5 samples from the food court UAI, 12 samples from vendors around the UAI, and 7 samples from fast-food restaurants in the area the Senayan. We culture bacteria samples on MacConkey media orders, then the bacteria identified by macroscopic morphology and microscopy to determine the presenc of E. coli. From this study, most samples contain E. coli, with the highest percentage found from street vendors around the UAI (98%), then from the food court UAI (87.20%), and the lowest (18.40%) came from fast food restaurants in the area the Senayan.